teaching and learning the competencies and skills of the Common National Curricular Base - Eliane Marques dos Santos (Universidade Estadual de Alagoas, 2020)
The objective of this article is to identify how the teaching of competences should be guided by the National Common Curricular Base, since it defines competencies, skills and learning and development objectives that explain the essential learning that all students must develop during basic education. The methodological path was the training of scholarship scholars and the development of interdisciplinary projects guided by the ten general competencies of BNCC with the use of active methodology for problematization adapted from the Arco de Maguerez. In this adaptation, the method has three stages: reality situations, theorization and application to reality. Methodological alternatives are exemplified with their essential characteristics for the teaching plan and the elaboration of interdisciplinary projects. The competence teaching and learning plan must contemplate the relationship between the components: competences, skills, content, pedagogical strategies and assessment. With this investigation, knowledge and methods supported in practice are also shared, with a view to configuring professional development that stimulates andencourages quality teaching work.